2013
DOI: 10.1016/j.chb.2012.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of social networking sites increase children’s risk of harm?

Abstract: Although research findings have been equivocal as to whether the use of social networking sites (SNS) increases experiences of online risk among children, the affordances of SNS lend support to this possibility, attracting much policy and public concern. The present article examines whether the use of such services increases the risks that children and young people encounter by analyzing data from a random stratified sample of approximately 1000 internet-using children aged 9-16 years in each of 25 European co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 48 publications
9
81
0
12
Order By: Relevance
“…An increase in risk awareness with respect to internet use among children confirmed that preteen age children were aware of risks of personal information disclosure, system security, data stealing, and contact with strangers (Livingstone, 2014;Lwin et al, 2012;W. Shin & Ismail, 2014;Staksrud et al, 2013). Based on these studies, risk is seen as an important construct in the study affected by the influences of parents and peers and having an important effect on the child's attitude to the use of technology.…”
Section: An Overview Of Previous Studiesmentioning
confidence: 80%
“…An increase in risk awareness with respect to internet use among children confirmed that preteen age children were aware of risks of personal information disclosure, system security, data stealing, and contact with strangers (Livingstone, 2014;Lwin et al, 2012;W. Shin & Ismail, 2014;Staksrud et al, 2013). Based on these studies, risk is seen as an important construct in the study affected by the influences of parents and peers and having an important effect on the child's attitude to the use of technology.…”
Section: An Overview Of Previous Studiesmentioning
confidence: 80%
“…Por otro lado, un amplio número de investigaciones sobre hábitos y experiencias de uso de las TIC se han centrado en poblaciones infantiles y juveniles (Chen, Hsiao, Chern & Chen, 2014;Livingstone & Helsper, 2007;Staksrud, Ólafsson & Livingstone, 2013), pocas en personas adultas (Godfrey & Johnson, 2009;Martinez-Pecino, Delerue & Silva, 2013;Pfeil, Arjan & Zaphiris, 2009), menos en mujeres (Castaño, 2009;Rubio y Escofet, 2013) y menos aún en mujeres de entornos rurales (Falk & Kilpatrick, 2000;Rebollo & Vico, 2014). Algunos informes advierten de las especiales dificultades que afrontan las comunidades rurales (LaRose, Gregg, Strover, Straubhaar & Carpenter, 2007;Novo-Corti, VarelaCandamio & García-Alvarez, 2014) y las personas mayores (Braun, 2013;Dias, 2012) en el acceso y uso de las tecnologías, señalando los múltiples factores que pueden incidir en su exclusión digital.…”
Section: │2unclassified
“…Internetiohte kogevad enim teismeeas lapsed, kes kasutavad internetti sagedamini, riskantselt ning kelle digitaalsed oskused on keskmisest paremad (Helweg-Larsen et al, 2012;Soo et al, 2012;Staksrud, Ólafsson, & Livingstone, 2013). Uurimistulemused näitavad, et rohkem saavad seksuaalse sisuga sõnumeid ja on küberkiusamise sihtmärgiks noored, kes suhtlevad sageli jututubades, MSNis või teistes suhtlusvõrgustikes, ning eriti need, kes suhtlevad võõrastega või räägivad seksuaalsetel teemadel (Baumgartner, Valkenburg, & Peter, 2010;De Graaf & Vanwesenbeeck, 2006;Mitchell, Finkelhor, & Wolak, 2001;Mitchell et al, 2007).…”
Section: Internetiohud Ja Kahju Kogemineunclassified